Transforming food systems in the Pacific: Stories from the field - Pye-Smith, Charlie (Technical Centre for Agricultural and Rural Cooperation, 2017)
Many islands import most of their food, much of which is calorie-dense and of low nutritional value. It may be cheaper than local produce, but a diet based on imported food is leading to a whole range of health problems. All too often, nutritious indigenous foods are ignored by local populations, as they are seen as ‘poor people’s food’. Tourism has been rapidly expanding in both regions, yet there is a disconnect between the tourist market and local producers. Indeed, 70% of the food used in the tourist industry in the Pacific is imported. As this booklet shows, creating closer links between tourism and agriculture – agritourism – can help to reduce the food import bill and at the same time boost local food production, and therefore the incomes of island farmers. With support from the intra-ACP Agricultural Policy Programme funded by the European Union, CTA has been actively promoting links between the two regions and encouraging them to share their knowledge and experience. On the one hand, CTA has provided policy support which has brought together government ministries with the private sector to promote agritourism. CTA also played a key role in establishing the Chefs for Development Initiative, which is creating closer links between the hospitality industry and local farmers. Over time, these endeavours will help to generate income and employment across the value chain.